Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1039/c5dt02859k
|View full text |Cite
|
Sign up to set email alerts
|

The structures of CyMe4-BTBP complexes of americium(iii) and europium(iii) in solvents used in solvent extraction, explaining their separation properties

Abstract: Graphical abstractThe structure around the absorbing atom in the dicomplexes of 6,6'-bis (5,5,8,8-tetramethyl-5,6,7,8-tetrahydro-benzo[1,2,4]triazin-3-yl) [2,2]bipyridine, CyMe4-BTBP, with americium(III) and europium(III) have been determined by means of Am and Eu L3 edge EXAFS spectroscopy in a series of solvents used to separate these metal ions using solvent extraction. The obtained structural information has been correlated with previously reported solubility and selectivity data as well as ionic radii in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 37 publications
1
22
1
Order By: Relevance
“…30 In addition, CyMe4-BTPhen 3 and CyMe4-BTBP 2 both form identical 1:2 complexes with Cm(III) as shown by TRLFS studies, 31 while CyMe4-BTBP 2 forms a 1:2 complex with Am(III) as shown by EXAFS studies. 32 A single bidentate nitrate ion completes the inner coordination sphere in the Am(III) and Cm(III) 1:2 complexes of both ligands 2 and 3, which is in agreement with the solution and solid state structures of the corresponding lanthanide(III) complexes of 2 and 3. 33 It thus seems likely that in the present study, CyMe4-BTPhen 3 forms structurally identical 1:2 complexes with both Am(III) and…”
Section: Separation Of Am(iii) From Cm(iii) By Hydrophobic Ligands Insupporting
confidence: 80%
“…30 In addition, CyMe4-BTPhen 3 and CyMe4-BTBP 2 both form identical 1:2 complexes with Cm(III) as shown by TRLFS studies, 31 while CyMe4-BTBP 2 forms a 1:2 complex with Am(III) as shown by EXAFS studies. 32 A single bidentate nitrate ion completes the inner coordination sphere in the Am(III) and Cm(III) 1:2 complexes of both ligands 2 and 3, which is in agreement with the solution and solid state structures of the corresponding lanthanide(III) complexes of 2 and 3. 33 It thus seems likely that in the present study, CyMe4-BTPhen 3 forms structurally identical 1:2 complexes with both Am(III) and…”
Section: Separation Of Am(iii) From Cm(iii) By Hydrophobic Ligands Insupporting
confidence: 80%
“…There is a report from Den Auwer on the Am(NO 3 ) 3 (TEMA) 2 complex, 72 another by Girnt on Am(NO 3 ) x (dmpbipy) x , 73 one by Bremer involving Am(NO 3 ) x (C5-BPP) x , 74 and finally Ekberg investigated [Am(NO 3 )(CyMe 4 -BTBP) 2 ] 2+ . 75 These studies showed an average Am–O NO 3 distance of 2.49 ± 0.01 Å. For Cm, numerous measurements have been made on NO 3 – species.…”
Section: Discussionmentioning
confidence: 98%
“…In solution, the europium(III) ion coordinates two BTBP ligands for a coordination number of eight, whereas a crystal structure precipitating from one of these solutions also includes a bidentately bound nitrate ion, making it effectively ten-coordinate [ 22 ]. Furthermore, when americium(III) was treated in the same way, it was found that the americium(III) ion thanks to its larger size coordinates a nitrate even in solution, and was determined to be at least nine-coordinate [ 23 ].…”
Section: Resultsmentioning
confidence: 99%